Near-freezing temperature storage enhances chilling tolerance in nectarine fruit through its regulation of soluble sugars and energy metabolism. (15th August 2019) - Zhao, Handong; Jiao, Wenxiao; Cui, Kuanbo; Fan, Xinguang; Shu, Chang; Zhang, Wangli; Cao, Jiankang; Jiang, Weibo
Highlights: NFT storage did not result in visual CI symptoms in nectarine fruit. NFT reduced sucrose degradation to enhance chilling tolerance in nectarine fruit. NFT-stored fruit showed higher activities of HXK and FRK. Chilling resistance in NFT-stored fruit was related to higher energy status. Abstract: To avoid chilling injury (CI) of nectarines during storage, the impact of near-freezing temperature (NFT) (−1.4 ± 0.1 °C), 0 ± 0.1 °C and 5 ± 0.1 °C on CI incidence, ion leakage, levels of soluble sugars and enzymatic activities related to soluble sugars and energy metabolism, were investigated over five weeks. NFT-stored fruit showed no CI symptoms and significantly ( P  < 0.05) lower increase of ion leakage than those kept at 0 and 5 °C. NFT significantly ( P  < 0.05) diminished the activities of sucrose metabolism-associated enzymes leading to a higher level of sucrose in fruit, and maintained higher activities of hexokinase and fructokinase. Additionally, NFT-stored fruit exhibited significantly ( P  < 0.05) higher activities of energy metabolism-associated enzymes than fruit stored at 0 and 5 °C, leading to high levels of adenosine triphosphate and energy in fruit. These results indicated that NFT storage can effectively enhance chilling tolerance of nectarine fruit by inducing the metabolism of soluble carbohydrates and energy.